The influence of amine structures on the stability and catalytic activity of gold nanoparticles stabilized by amine-modified hyperbranched polymers. (5th January 2018) - Dong, Hui; Dai, Yu; Zhang, Xiaojin; Zhang, Zhenguo; Fu, Shuangli; Zhong, Zhenlin
Abstract: Amine-modified amphiphilic hyperbranched polymers (MePEG-H104-N x ) were prepared from hyperbranched 2, 2-bis(methylol)propionic acid polyester (H104) by decoration with polyethylene glycol monomethyl ether (MePEG) and different classes of oligo(ethylenimine)s. By using the MePEG-H104-N x polymers as stabilizers, gold nanoparticles (AuNPs) were prepared in an aqueous medium by the reduction of HAuCl4 with NaBH4 . The AuNPs were sphere-like with diameters of 2–4 nm, which were dependent on the structure of the amines. Further, the catalytic activity of these AuNPs was evaluated by monitoring the reduction reaction of 4-nitrophenol by sodium borohydride. The results demonstrate that the longer chain length and the branched structure of the amine moieties are beneficial for the stability and catalytic activity of the AuNPs. The AuNPs stabilized by MePEG-H104-N4 and MePEG-H104-Nb3 showed high catalytic activity for the reduction of 4-nitrophenol to 4-aminophenol.